2002
DOI: 10.1023/a:1023067728557
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sporadic amyotrophic lateral sclerosis associated with seropositivity for herpesviruses and echovirus-7

Abstract: We examined the association between risk of sporadic amyotrophic lateral sclerosis (ALS) and seroprevalence of antibodies to echovirus-7 (echo-7) and herpesviruses 6, 7, and 8 through a population-based case-control study. We enrolled in a northern Italy area 20 newly diagnosed ALS cases and 20 referents. Risk of ALS was higher in subjects seropositive for echo-7 when we used the immunofluorescent assay, while little increase was noted with the neutralization test. Considering the different characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…Starting from the pioneer study by Bowery [1] showing the neurodegenerative effects produced by tetanus toxin in rats, a significant emerging body of literature suggests the possibility that CNS infections may play a cofactorial role in inducing neurodegenerative diseases [2]. Serological studies suggest a potential involvement of enteroviruses (EV) and human herpesviruses (HHV) in the aetiology of ALS, a fatal neurodegenerative disease selectively affecting motor neurons [3]. A viral origin of PD has also been proposed on the basis of the close similarity between the clinical symptoms of PD and those of Japanese encephalitic virus [4].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the pioneer study by Bowery [1] showing the neurodegenerative effects produced by tetanus toxin in rats, a significant emerging body of literature suggests the possibility that CNS infections may play a cofactorial role in inducing neurodegenerative diseases [2]. Serological studies suggest a potential involvement of enteroviruses (EV) and human herpesviruses (HHV) in the aetiology of ALS, a fatal neurodegenerative disease selectively affecting motor neurons [3]. A viral origin of PD has also been proposed on the basis of the close similarity between the clinical symptoms of PD and those of Japanese encephalitic virus [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Gulf War veterans there was a significant association between systemic mycoplasmal infections and ALS (Nicolson et al, 2002), although it was not established if mycoplasma plays a role in the pathogenesis of ALS or if ALS patients are more susceptible to ALS. The results of another study suggested an association between the risk of ALS and infection with certain enteroviruses and herpes virus (Cermelli et al, 2003).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 96%
“…Arguably one of the most studied and most conflicting series of results is that regarding the potential viral aetiology of ALS [82][83][84]. Suspected culprits include polioviruses [85], enteroviruses [85][86][87][88][89][90], herpesviruses (HHV-6, HHV-7, HHV-8 [91][92][93]), echoviruses (ECHO6 and ECHO7 [92,94]), and even human endogenous retroviruses [95]. This line of inquiry is likely spurred by the continued findings of reverse transcriptase activity in patients with ALS [96,97] and reversible ALS-like symptoms that are sometimes observed in HIV patients [98][99][100][101].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%